Development of DNA Markers From Physically Mapped Loci in Aegilops comosa and Aegilops umbellulata Using Single-Gene FISH and Chromosome Sequences - Said, Mahmoud; Holušová, Katerina; Farkas, András; Ivanizs, László; Gaál, Eszter; Cápal, Petr; Abrouk, Michael; Martis-Thiele, Mihaela M.; Kalapos, Balázs; Bartoš, Jan; Friebe, Bernd; Doležel, Jaroslav; et al. (Frontiers in Plant Science, 2021)
Breeding of agricultural crops adapted to climate change and resistant to diseases and pests is hindered by a limited gene pool because of domestication and thousands of years of human selection. One way to increase genetic variation is chromosome-mediated gene transfer from wild relatives by cross hybridization. In the case of wheat (Triticum aestivum), the species of genus Aegilops are a particularly attractive source of new genes and alleles. However, during the evolution of the Aegilops and Triticum genera, diversification of the D-genome lineage resulted in the formation of diploid C, M, and U genomes of Aegilops. The extent of structural genome alterations, which accompanied their evolution and speciation, and the shortage of molecular tools to detect Aegilops chromatin hamper gene transfer into wheat. To investigate the chromosome structure and help develop molecular markers with a known physical position that could improve the efficiency of the selection of desired introgressions, we developed single-gene fluorescence in situ hybridization (FISH) maps for M- and U-genome progenitors, Aegilops comosa and Aegilops umbellulata, respectively. Forty-three ortholog genes were located on 47 loci in Ae. comosa and on 52 loci in Ae. umbellulata using wheat cDNA probes. The results obtained showed that M-genome chromosomes preserved collinearity with those of wheat, excluding 2 and 6M containing an intrachromosomal rearrangement and paracentric inversion of 6ML, respectively. While Ae. umbellulata chromosomes 1, 3, and 5U maintained collinearity with wheat, structural reorganizations in 2, 4, 6, and 7U suggested a similarity with the C genome of Aegilops markgrafii. To develop molecular markers with exact physical positions on chromosomes of Aegilops, the single-gene FISH data were validated in silico using DNA sequence assemblies from flow-sorted M- and U-genome chromosomes. The sequence similarity search of cDNA sequences confirmed 44 out of the 47 single-gene loci in Ae. comosa and 40 of the 52 map positions in Ae. umbellulata. Polymorphic regions, thus, identified enabled the development of molecular markers, which were PCR validated using wheat-Aegilops disomic chromosome addition lines. The single-gene FISH-based approach allowed the development of PCR markers specific for cytogenetically mapped positions on Aegilops chromosomes, substituting as yet unavailable segregating map. The new knowledge and resources will support the efforts for the introgression of Aegilops genes into wheat and their cloning.